Digital Literacy Movement Through Training Making Animated Videos Of Rejang Lebong Folk Stories - Dian Ramadan Lazuardi; Nyayu Masnun Arief (Abdimas Paspama, 2024)
The Digital Literacy Movement through Training in Making Rejang Lebong Folklore Animation Videos aims to increase digital literacy among teenagers, especially in developing digital content creation skills based on the Rejang Lebong folklore. The problem currently faced by partners is that teenagers are not using gadgets optimally, gadgets are only used as a means of entertainment such as using social media, playing games, etc. One solution to this problem is by implementing a Digital Literacy Movement through Training in Making Rejang Lebong Folklore Animation Videos. This training was carried out by teaching techniques for making animated videos using the Benime application, which is a simple but effective platform for creating narrative-based animations. In this training, participants are introduced to the basic steps for making videos, processing images and sound for animated stories. Participants are given direct tutorials and practical guidance to create animated videos of the Rejang Lebong folklore, with the hope of preserving and introducing the richness of regional culture to a wider audience in a modern way. By converting folklore into an animated format, participants not only learn about creating digital content, but also gain knowledge about how to package local culture in a form that is more modern and attractive to the younger generation. This is expected to reduce the gap between traditional culture and technology, as well as encourage the younger generation to care more about local culture. The next stage of the plan is to form a digital creative community that is open to all training participants, form collaboration with the media to disseminate participants' work, organize a digital cultural festival which will feature animated folk tales from Rejang Lebong and other areas and continue this service by creating animated videos with the theme different.